Pengaruh pola asuh orang tua terhadap anak dalam mengenalkan Bahasa Arab di era digital - Ula, Aristya Luna Rahmatul (Maliki Interdisciplinary Journal, 2024)
The writing of this article was motivated by the increasing public attention to Arabic language learning. This is marked by the increase in language teachers, schools, and early childhood education institutions based on Islam. However, the role of teachers in schools alone is not enough to introduce foreign languages. Parents as the first school for their children also have a very big share in that. they must understand the right parenting style to maximize the child’s learning language potential. Parenting or parenting is a certain style that every parent has to nurture, educate, and discipline children to form behavior or behavior by societal norms. The objectives of this article include: 1) describing how the influence of parenting on children’s ability to introduce foreign languages. 2) Educating parents about parenting methods that are effective in introducing foreign languages to children, especially Arabic. 3) Implementation of the use of digital technology in introducing Arabic. This article uses the method of literature review or literature study which contains a collection of data or theories relevant to research problems sourced from various media such as articles, journals, books, theses, and others. These sources are used as reference material in conducting this research. The results of the study showed that the influence of parenting style, including the language learning model applied, the level of consistency, and parental support or motivation has a close and significant relationship with children’s ability to understand Arabic. This research is expected to provide insights that can be useful for parents, educators, and researchers in developing effective strategies to introduce Arabic to children early in the digital era like today.